The Influence of Chitosan on the Physical Properties of Avocado Seed Starch-Based Biofoam (Biosaintifika: Journal of Biology & Biology Education, 2026)
The global reliance on styrofoam has left us with a crisis of non-biodegradable waste. To tackle this, our study explores a sustainable alternative, i.e., converting avocado seeds, which are an overlooked agricultural byproduct, into biodegradable foam (biofoam). We focused on characterizing avocado seed starch and investigating how the addition of chitosan influences the foam’s physical performance. The properties observed in this research include tensile strength testing with a universal mechanical tester, microstructure analysis using SEM, biodegradability, and water absorption. In addition, characteristics of the starch, including granule size and shape using a polarized microscope, and crystallinity using XRD, were also analyzed. Our analysis revealed that the starch granules are primarily spherical (7.2–41.7 µm) with a B-type crystalline structure. By incorporating 20% chitosan, we observed a significant structural shift from uniform globular cells to a bubble-like matrix, which tripled the material’s tensile strength from 0.07 MPa to 0.263 MPa. Furthermore, the chitosan acted as a vital functional filler, reducing water sensitivity and slowing the rate of biodegradation to more practical levels. These results offer a compelling case for materials science: we can transform food waste into high-performance, eco-friendly packaging. By aligning with UN Sustainable Development Goal (SDGs) 12 (Responsible Consumption and Production), this research provides a tangible pathway toward a circular economy, proving that the future of plastics might just be hidden in our organic waste. Using avocado seed waste to produce starch, a raw material for creating eco-friendly biofoam, promotes sustainable production and consumption patterns.